A Critical Theoretical Approach to Cancer Disparities: Breast Cancer and the Social Determinants of Health - Sarah Gehlert; Darrell Hudson; Tina Sacks (Frontiers Media S.A., 2021)
Breast cancer is the most commonly experienced cancer among women. Its high rates of incidence and survival mean that a number of women will live it for periods of their lifetimes. Group differences in breast cancer incidence and mortality occur by race and ethnicity. For example, while white women are slightly more likely to be diagnosed with breast cancer, Black women are 40% more likely to die from the disease. In this article, rather than focusing the discussion on individual-level factors like health behaviors that have the potential to blame Black women and those living in poverty for their conditions, we view breast cancer disparities through the lens of Critical Race Theory, taking a historical perspective. This allows us to delve beyond individual risk factors to explore social determinants of breast cancer disparities at the population level, paying special attention to the myriad ways in which social factors, notably views of race and discriminatory public policies, over time have contributed to the disproportionate breast cancer mortality experienced by Black women. We suggest ways of addressing breast cancer disparities, including methods of training healthcare professionals and public policy directions, that include rather than marginalize Black and lower socioeconomic status women.